2012
DOI: 10.1159/000338814
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Cardiomyopathy in Sweden: Evidence for Different Ethnic Predisposition and Altered Cardio-Circulatory Status

Abstract: <b><i>Background:</i></b> In this paper, we report about new insights regarding clinical course, long-term outcome, ethnic/genetic predisposition and cardio-circulatory status in the large stress-induced cardiomyopathy (SIC) cohort from Sweden. <b><i>Methods and Results:</i></b> We have included 115 consecutive SIC patients between January 2005 and January 2010 at Sahlgrenska University Hospital in Gothenburg. Hemodynamic status and sympathetic nerve activity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 55 publications
3
53
0
4
Order By: Relevance
“…A meta-analysis published in 2014 has described that in a 2-year follow-up, 3-8% of TTC patients had recurring its symptoms; requiring particular attention for this fact (7,8,(69)(70)(71)(72). Different LV wall motion disorders in the same patient are also reported; that is, wall motion disorder patterns are not always the same (73,74).…”
Section: Recurrencementioning
confidence: 99%
“…A meta-analysis published in 2014 has described that in a 2-year follow-up, 3-8% of TTC patients had recurring its symptoms; requiring particular attention for this fact (7,8,(69)(70)(71)(72). Different LV wall motion disorders in the same patient are also reported; that is, wall motion disorder patterns are not always the same (73,74).…”
Section: Recurrencementioning
confidence: 99%
“…4 However a significant minority of patients have less favorable outcomes, with in-hospital mortality of approximately 0.5-1% from cardiogenic shock and multiorgan failure. 53 …”
Section: -7 Daysmentioning
confidence: 99%
“…In their article in this issue of Cardiology , entitled, ‘Stress-Induced Cardiomyopathy in Sweden: Evidence for Different Ethnic Predisposition and Altered CardioCirculatory Status’, Schultz et al [7] reported the clinical features and hemodynamic function in stress-induced cardiomyopathy (SIC) in Sweden. In their study, 115 patients were diagnosed with SIC from a large cohort studied over 5 years.…”
mentioning
confidence: 99%
“…Another study, published last year, investigated the differences in baseline characteristics between African-Americans and non-African-Americans [9], reporting no racial differences except electrocardiographic findings. Meanwhile, Schultz et al [7] reported that the recurrence rate of SIC was over 13%, which surpasses the previous highest rate of approximately 11% [10]. The recurrence rate of SIC in the largest Japanese cohort is 2% [11]; therefore, further genetic investigation is required to clarify the high predominance and recurrence rate in the Swedish cohort.…”
mentioning
confidence: 99%
See 1 more Smart Citation